Increasing Teacher Professional Competence in Developing Procedural Abilities Using the Application of Assessment of Integrated Science Using Mobile Learning on Android Platform Gadgets - Allesius Maryanto; Dadan Rosana; Didik Setyawarno (Universitas Negeri Yogyakarta, 2020)
The development of smart mobile phone terminals, mobile learning has become an effective and efficient way for teachers to learn, so that the continuous development of teacher competency development can take place in a fun way. From the aspect of integrated science learning material, it is very clear that science learning in the 2013 curriculum is carried out on an integrated basis. Integrative science has the meaning of combining various aspects, namely the domains of attitudes, knowledge and skills. Therefore, the assessment system developed in science learning must also be able to develop four dimensions of knowledge (factual, conceptual, procedural). In this study, procedural knowledge was specifically developed using the assessment of integrated science application using mobile learning on gadgets with the android platform. The methodology developed in this study is a Research and Development spiral model as referenced by Cennamo and Kalk (2005: 6). In this spiral model, there are 5 (five) development phases, namely: (1) definition, (2) design, (3) demonstration, (4) develop, and (5) presentation (deliver). The research results that have been achieved are; (1) A model for enhancing the professional competence of teachers in the development of procedural ability tests through the design of an assessment of integrated science using mobile learning on gadgets with a proper android platform based on expert judgemnet, (2) Practicality tests of the model have been carried out based on the results of training involving junior high school teachers in the MGMP area of science teachers, Mlati District, Sleman Regency, (3) The model is effective in improving students' procedural abilities